Analisis Penerapan Faktor-Faktor Green Supply Chain pada Proyek Konstruksi Gedung di Kota Palangka Raya - Pradila, Mitha; Uda, Subrata Aditama Kittie Aidon; Waluyo, Rudi (Universitas Batanghari Jambi, 2024)
Climate change due to increased greenhouse gas emissions and resource depletion is one of the biggest challenges of the 21st century. The construction sector contributes to economic development by providing equipment and physical infrastructure. However, there are negative impacts such as waste generation and environmental pollution, especially in developing countries. Green supply chain as a way to reduce the negative environmental impact of construction projects. Green supply chain practices are considered as environmentally friendly practices that include water efficiency, energy efficiency, waste management, environmental conservation, recycling and reuse. But the lack of research on green supply chains has led to very little information about the application of green supply chains in building construction projects. The purpose of this study was to determine and analyze the dominant factors in the application of green supply chain factors in building construction projects in Palangka Raya City. This research uses quantitative descriptive methods and data collection in the form of surveys and distributes questionnaires to 36 contractors with a return rate of 89%. This study identified 68 green supply chain factors applied to building construction projects in Palangka Raya City. The results showed three dominant factors in the application of green supply chain factors in building construction projects in Palangka Raya City as a whole: There are performance evaluations for workers, Quality testing is carried out on installed mechanical and electrical installations, There are SOPs for work control and supervision.